Nanoparticle drug delivery systems for synergistic delivery of tumor therapy - Chen, Daoyuan; Liu, Xuecun; Lu, Xiaoyan; Tian, Jingwei (Frontiers in Pharmacology, 2023)
Nanoparticle drug delivery systems have proved anti-tumor effects; however, they are not widely used in tumor therapy due to insufficient ability to target specific sites, multidrug resistance to anti-tumor drugs, and the high toxicity of the drugs. With the development of RNAi technology, nucleic acids have been delivered to target sites to replace or correct defective genes or knock down specific genes. Also, synergistic therapeutic effects can be achieved for combined drug delivery, which is more effective for overcoming multidrug resistance of cancer cells. These combination therapies achieve better therapeutic effects than delivering nucleic acids or chemotherapeutic drugs alone, so the scope of combined drug delivery has also been expanded to three aspects: drug-drug, drug-gene, and gene-gene. This review summarizes the recent advances of nanocarriers to co-delivery agents, including (i) the characterization and preparation of nanocarriers, such as lipid-based nanocarriers, polymer nanocarriers, and inorganic delivery carriers; (ii) the advantages and disadvantages of synergistic delivery approaches; (iii) the effectual delivery cases that are applied in the synergistic delivery systems; and (iv) future perspectives in the design of nanoparticle drug delivery systems to co-deliver therapeutic agents.